Kompetence Celní správy České republiky - Klimtová, Petra, 1984-; Masarykova univerzita. Katedra finančního práva a národního hospodářství (2015)
Rigorózní práce deskripcí a analýzou stávajících kompetencí Celní správy České republiky hledá odpověď na otázku, zda lze i po vstupu České republiky do Evropské unie výkon celního dohledu a správu cel a daní souvisejících s přechodem zboží přes státní hranice, považovat za dominantní funkci celních orgánů. V historických souvislostech jsou postupně identifikovány tyto základní kompetence celní správy: správa cel, daně z přidané hodnoty, spotřebních a ekologických daní, dělená správa, činnost celní správy jako orgánu činného v trestním řízení a souborná kategorie ostatních kontrolních činností. Jednotlivé kompetence jsou popsány z hlediska procesů v nich probíhajících. Závěrečná část práce je věnována očekávanému funkčnímu vývoji celní správy.
This doctoral dissertation thesis uses the description methods and analysis to define the current competences of the Customs Administration of the Czech Republic to seek an answer to the question if the performance of the customs supervision and administration of customs and taxes related to the transfer of goods across the borders can be interpreted as the dominant function of the customs bodies even after the Czech Republic joined the European Union. In the context of history, the following basic competences of the customs administration were identified: customs administration, value added tax administration, excise duties and ecological taxes, divided administration, activities of the customs administration as an investigative, prosecuting and adjudicating body and the complex category of other inspection activities. The individual competences are described from the point of view of the ongoing processes. The final part of the dissertation thesis is focused on the anticipated development of the customs administration.
Rigorózní práce (JUDr.)--Masarykova univerzita, Právnická fakulta, 2015
Anglické resumé
Keywords: Česko. -- Celní správa; celní řízení; celní správa; cla; customs procedure; tariff administration; tariff; Česko; Czechia; rigorózní práce; doctoral dissertations